Psychosocial needs of hospitalized and non-hospitalized Filipino cancer patients. - Rana, Nieves O.
The total understanding of the needs of a patient in his social and cultural millieu is the basic and foremost purpose of an organized health care. This study hopes to contribute to the body of scientific knowledge on the psychosocial needs of Filipino cancer patients. The findings of this study will equip nurses specializing in the cancer nursing with the knowledge and understanding of the specific psychosocial needs of cancer patients thereby enabling them to formulate a realistic, adequate and effective nursing care plan. The cancer patients will be most benefitted. Hopefully they will receive the kind of care they expect/deserve. The study was conducted at the Philippine General Hospital and administered to 100 hospitalized and non-hospitalized cancer patients selected at random. Research instruments consisted of an interview schedule and checklist. Utilizing Maslow's hierarchy of needs as a model, the questionnaire gathered data on the specific psychosocial needs of cancer patients. Statistical analysis of the data was done through the use of the Chi-square the contingency coefficient and McNemar test. Findings showed various similarities in the psychosocial needs of cancer patients. However, there appeared differences in the magnitude of perception of psychosocial needs between hospitalized and non-hospitalized subjects. Hospitalized cancer patients have increased psychosocial needs in terms of safety and security, love and belonging, self-esteem and recognition compared to non-hospitalized cancer patients. The magnitude of difference ranged from (.216-.691). Other findings revealed that socio-demographic variables such as age, sex, educational attainment, religion, closeness of family ties, have no significant relationship with the psychosocial needs of hospitalized and non-hospitalized cancer patients. The knowledge of diagnosis of the respondents was found to be significantly related to safety and security needs (p .01). In terms of the perception of care received by the hospitalized group, majority of the samples felt that they were provided with only "slight" degree of care in the physical and emotional needs. Hospitalized cancer patients were treated with respect by hospital personnel. The findings of the study imply a need for health workers, specifically the nurses, to identify psychosocial needs of patients and to formulate a plan care relevant to such needs. On top of this, care planning must be carried out to effect quality care considering that the patient is a biopsychosocial being.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Cancer -- Nursing; Cancer patients -- Rehabilitation